The Impact of the Digital Hijrah Trend on the Lifestyle of Millennial Muslims in the Social Media Era - Fitrianingsih (Jurnal Ar Ro'is Mandalika (Armada), 2024)
The phenomenon of digital hijrah has emerged as a significant trend among millennial Muslims in the era of social media. This study aims to analyze the impact of digital hijrah on the lifestyle of Muslim millennials through qualitative methods, particularly using literature review and library research. Digital hijrah refers to a transformative shift in religious identity, where individuals seek a deeper understanding of Islam, often facilitated by the use of social media platforms such as Instagram, YouTube, and TikTok. This research explores how digital hijrah influences various aspects of lifestyle, including fashion preferences, consumption patterns, social interactions, and spiritual practices. By analyzing existing studies, scholarly articles, and relevant digital content, this paper identifies that social media plays a dual role as both a source of inspiration and a platform for self-representation among Muslim millennials. The findings indicate that digital hijrah encourages the adoption of modest fashion, the proliferation of halal products, and increased participation in virtual Islamic communities. However, it also highlights potential challenges, such as identity conflicts and over-reliance on digital figures for religious guidance. This study contributes to understanding how modern technology reshapes religious expressions and practices in contemporary Muslim societies. The research emphasizes the need for critical awareness in consuming digital content while fostering a balanced integration of modernity and Islamic values.